Trouble ahead - the subprime crisis as evidence of a new regime in the stock market - Araújo, Tanya (2010)
In August 2007, the crisis of the subprime mortgage industry stormed the financial systems of several countries. As a response, hundreds of billions of dollars were injected by the authorities into the market. Nevertheless, this was not enough to avoid the second wave of the subprime crisis, as revealed by the fall of the S&P500 stock index since January 2008. In spite of the important achievements obtained in finance theory, the conventional wisdom on the inexistence of structure in the evolution of stock markets still prevails. The Efficient Market Hypothesis view ([1],[2]) assesses the evolution of financial markets as the result of a Brownian process. More recently, the contributions of econophysicists ([3],[4],[5]) have challenged the dominance of randomness. Using a stochastic geometry technique, here we show that the dynamics of the S&P500 set of stocks defines a structure, which is specifically shaped by the occurrence of crises. A new coefficient is defined in order to capture the structural changes occurring on the S&P500 set of stocks. This coefficient highlights an important modification of the dynamics of the 253 firms represented in the S&P500 and acting in the market for the period August 1988-January 2008, and situates the turbulence since the Summer 2007 as replica of a larger structural change going on for a decade.